Liposomal Nanomedicine: Applications for Drug Delivery in Cancer Therapy - Foad Rommasi; Neda Esfandiari (Nanoscale Research Letters, 2021)
Abstract The increasing prevalence of cancer, a disease in which rapid and uncontrollable cell growth causes complication and tissue dysfunction, is one of the serious and tense concerns of scientists and physicians. Nowadays, cancer diagnosis and especially its effective treatment have been considered as one of the biggest challenges in health and medicine in the last century. Despite significant advances in drug discovery and delivery, their many adverse effects and inadequate specificity and sensitivity, which usually cause damage to healthy tissues and organs, have been great barriers in using them. Limitation in the duration and amount of these therapeutic agents’ administration is also challenging. On the other hand, the incidence of tumor cells that are resistant to typical methods of cancer treatment, such as chemotherapy and radiotherapy, highlights the intense need for innovation, improvement, and development in antitumor drug properties. Liposomes have been suggested as a suitable candidate for drug delivery and cancer treatment in nanomedicine due to their ability to store drugs with different physical and chemical characteristics. Moreover, the high flexibility and potential of liposome structure for chemical modification by conjugating various polymers, ligands, and molecules is a significant pro for liposomes not only to enhance their pharmacological merits but also to improve the effectiveness of anticancer drugs. Liposomes can increase the sensitivity, specificity, and durability of these anti-malignant cell agents in the body and provide remarkable benefits to be applied in nanomedicines. We reviewed the discovery and development of liposomes focusing on their clinical applications to treat diverse sorts of cancers and diseases. How the properties of liposomal drugs can be improved and their opportunity and challenges for cancer therapy were also considered and discussed. Graphic abstract